COMPARISON OF EFFECTIVENESS OF COMBINATION ANTIHYPERTENSION THERAPY IN WOMEN WITH ABDOMINAL OR GLUTEO-FEMORAL OBESITY - V. V. Skibitsky; S. V. Skibitskaya; A. V. Fendrikova; N. V. Porodenko (Российский кардиологический журнал)
Aim. To study the influence of combinational antihypertension therapy including inhibitor of angiotensin converting enzyme (ACEi) or direct renin inhibitor (DRI) on the parameters of 24-hour blood pressure monitoring (ABPM) in postmenopausal women in different obesity patterns.Material and methods. Totally, 168 women studied with arterial hypertension (AH) in postmenopause: 97 with abdominal obesity (AO) and 71 with gluteofemoral (GFO). Patients were randomized to groups of ACEi therapy and diuretic or DRI and diuretic. Follow-up lasted for 24 weeks.Results. In 4 weeks of therapy with the usage of maximal ACEi dosages, target level of blood pressure (BP) was reached in 30 from 42 (71,4%) women with AO and 27 from 32 (84,4%) with GFO, and maximum dose of DRI led to target pressure achievement in 37 from 41 (90,2%) women with AO and 30 from 33 (90,9%) with GFO. Others required addition to the therapy a dihydropyridine calcium antagonist. In 6 months of therapy in all groups of patients there was positive dynamics of the main 24-hour profile parameters.Conclusion. Combination of ACEi or DRI with indapamide retard have significant antihypertension effect in women with AH in AO and GFO. In addition, combination of DRI with diuretic is better than of ACEi that was showed by the prevalence and speed of target BP achievement, more significant dynamics of ABPM parameters and positive changes in patients spread upon physiologic and pathologic types of 24-hour profile in 24-week therapy, especially in AO.